Jovita wore pants : the story of a Mexican freedom fighter - Salazar, Aida (Scholastic Press, 2023)
"Jovita didn't want to cook and clean like her sisters, and she especially didn't want to wear the skirts her abuela gave her. She wanted to race her brothers and climb the tallest mesquite trees in Rancho Palos Blancos, ride horses, and wear pants! When her father and brothers joined the Cristeros War to fight for the right to practice religion, she wanted to help. She wasn't allowed to fight, but that didn't stop her from observing how her father strategized and familiarizing herself with the terrain. When tragedy struck, she did the only thing that felt right to her--cut her hair, donned a pair of pants, and continued the fight, commanding a battalion who followed her without question. Jovita Wore Pants is the story of a trailblazing revolutionary who fought for her freedom, told by her great niece, bestselling author Aida Salazar, and illustrated by Molly Mendoza"--